2012
DOI: 10.1098/rspb.2012.1817
|View full text |Cite
|
Sign up to set email alerts
|

Auditory sequence analysis and phonological skill

Abstract: This work tests the relationship between auditory and phonological skill in a non-selected cohort of 238 school students (age 11) with the specific hypothesis that sound-sequence analysis would be more relevant to phonological skill than the analysis of basic, single sounds. Auditory processing was assessed across the domains of pitch, time and timbre; a combination of six standard tests of literacy and language ability was used to assess phonological skill. A significant correlation between general auditory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 82 publications
8
69
2
Order By: Relevance
“…This is consistent with our previous findings, in which the correlations between rhythm processing and language skills were relatively independent of non-verbal intellectual skill in early adolescence and early adulthood (Grube et al, 2012, 2013). That is, these correlations were less affected by partialling out the effects on non-verbal IQ than those for pitch processing or processing speed (e.g., Deary, 1994; Stewart et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with our previous findings, in which the correlations between rhythm processing and language skills were relatively independent of non-verbal intellectual skill in early adolescence and early adulthood (Grube et al, 2012, 2013). That is, these correlations were less affected by partialling out the effects on non-verbal IQ than those for pitch processing or processing speed (e.g., Deary, 1994; Stewart et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…We found that both frequency discrimination and interval discrimination are correlated with reading-related skills, as reported previously (e.g., [4,6,7,9,12,17]). These correlations remained significant when covariance with reasoning ability (assessed with Raven’s Matrices, a visual-spatial test) was controlled for.…”
Section: Discussionsupporting
confidence: 89%
“…Although many studies reported significant correlations between reading-related skills and auditory skills (e.g., [1,2,4-17]), others failed to find such correlations [18-25]. More specifically, whereas in several studies, pitch processing was found to account for significant variance in reading skills (e.g., [1,9,17]), this was not the case in other studies (e.g., [25,26]). This discrepancy was attributed to differences in the types of perceptual tasks used [27-29] or to differences in the characteristics of the sampled populations [12,30].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies suggest that rhythm discrimination is associated with phonological processing222350515253. Corroborating these results, we observed a significant correlation between rhythm discrimination and phonological awareness.…”
Section: Discussionsupporting
confidence: 87%